Covalent Trapping of Methyllycaconitine at the α4-α4 Interface of the α4β2 Nicotinic Acetylcholine Receptor: ANTAGONIST BINDING SITE AND MODE OF RECEPTOR INHIBITION REVEALED - Absalom, Nathan L. (American Society for Biochemistry and Molecular Biology, 2013)
The α4β2 nicotinic acetylcholine receptors (nAChRs) are widely expressed in the brain and are implicated in a variety of physiological processes. There are two stoichiometries of the α4β2 nAChR, (α4)(2)(β2)(3) and (α4)(3)(β2)(2,) with different sensitivities to acetylcholine (ACh), but their pharmacological profiles are not fully understood. Methyllycaconitine (MLA) is known to be an antagonist of nAChRs. Using the two-electrode voltage clamp technique and α4β2 nAChRs in the Xenopus oocyte expression system, we demonstrate that inhibition by MLA occurs via two different mechanisms; that is, a direct competitive antagonism and an apparently insurmountable mechanism that only occurs after preincubation with MLA. We hypothesized an additional MLA binding site in the α4-α4 interface that is unique to this stoichiometry. To prove this, we covalently trapped a cysteine-reactive MLA analog at an α4β2 receptor containing an α4(D204C) mutation predicted by homology modeling to be within reach of the reactive probe. We demonstrate that covalent trapping results in irreversible reduction of ACh-elicited currents in the (α4)(3)(β2)(2) stoichiometry, indicating that MLA binds to the α4-α4 interface of the (α4)(3)(β2)(2) and providing direct evidence of ligand binding to the α4-α4 interface. Consistent with other studies, we propose that the α4-α4 interface is a structural target for potential therapeutics that modulate (α4)(3)(β2)(2) nAChRs.